The adaptability of Monday.com's app-based software: Discover the company building a flexible business model that adapts to individual company needs. Issue 2 (4th October 2022) - Manko, Barbara A
The tools of running a business are big business themselves. Finding a way to efficiently streamline processes could save time, effort, and money, but getting to that point often requires retraining and fitting the process to the software rather than the software to the process. Having an all-in-one platform that adapts to business needs is the novel way some companies have begun to approach productivity tools, with Monday.com being a prime example of where the technology is leading. An easy-to-use interface depends on the user's ability to grasp its setup, and by making an app-based platform, the founders are capitalizing on the iPhone generation. Monday.com is a prime example of a business offering a product for other businesses, and studying how they developed their software not only allows students to understand how such a tool can be useful in running a business, but also the innovative process behind creating a whole new way to do business.